Experimental evaluation of collection, thermal, and conductivity efficiency of a solar distiller pond as a free concentration unit in wastewater treatment process. Issue 5 (29th August 2018) - Farahbod, Farshad; Omidvar, Mohammadnabi
Abstract: The performance of one solar pond as a passive step in distilled and potable water production from desalination effluent is surveyed in this research. This solar pond is proposed in a zero discharge desalination process to prevent the salinity shocking which is made by a brackish water stream that exists from desalination units. The solar pond performance is evaluated by measuring three types of efficiency, experimentally, and mathematically. The efficiencies which are defined and calculated from experimental data are conductivity efficiency, thermal efficiency, and water recovery efficiency. The mathematical results are verified by experimental data which has been obtained during a year. The theoretical modelings show very good agreement with experimental data, especially for water collection and conductivity efficiency evaluation. The relative error of theoretical and experimental results for thermal efficiency evaluation through the day and night is obtained 7.2% and 4.9%, respectively. Abstract : Performance of one solar distiller pond as a passive step in distilled water production from desalination effluent is surveyed. The solar pond performance is evaluated experimentally and mathematically. Thermal efficiency through the day and night is obtained with 7.2% and 4.9% of relative error, respectively. There is good agreement between experimental and theoretical data of collection efficiency.